Makna Tradisi Khanduri Beureuat Bagi Masyarakat Gampong Uteuen Gathom, Bireuen, Aceh - Ahmad, Muhammad Yunus; Sari, Putri Izzah; Ikhwan, Ikhwan; Daud, Anwar (Sociology Department Of Syiah Kuala University, 2024)
Khanduri Beureuat is a tradition preserved to welcome the night of Nisfu Syaban. The Acehnese refer to this feast as Khanduri Beureuat because the word Beureuat means blessing, aligning with the purpose of the feast, which is to seek blessings from Allah SWT. Khanduri Beureuat is held on the night of Beureuat, which is the fourteenth day or the night entering the fifteenth of the month of Syaban. This study aims to analyze the celebration of Khanduri Beureuat (Nisfu Syaban Feast) in Gampong Uteuen Gathom, Bireuen, and to reveal the significance of this tradition for the local community. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings indicate that the celebration of Khanduri Beureuat is a tradition of the Muslim community in Aceh, particularly in Gampong Uteuen Gathom, Bireuen Regency, carried out from generation to generation. Khanduri Beureuat is held on the night of Beureuat, which is the fourteenth day or the night entering the fifteenth of the month of Syaban. This tradition encompasses various values such as Islamic teachings, humanity, morality, and culture, and it strengthens family bonds, solidarity, and social ties among the residents of Gampong Uteuen Gathom, Bireuen, Aceh.AbstrakKhanduri Beureuat merupakan tradisi yang dilestarikan untuk menyambut malam Nisfu Syaban. Masyarakat Aceh menyebut khanduri ini sebagai Khanduri Beureuat karena kata Beureuat berarti berkah, sesuai dengan tujuan pelaksanaan khanduri ini yaitu untuk mengharap keberkahan dari Allah SWT. Khanduri Beureuat dilaksanakan pada malam Beureuat, yaitu hari keempat belas atau memasuki malam kelima belas bulan Syaban.Penelitian ini bertujuan untuk menganalisis perayaan Khanduri Beureuat (Khanduri Nisfu Syaban) di Gampong Uteuen Gathom, Bireuen, serta mengungkapkan makna tradisi tersebut bagi masyarakat setempat. Penelitian ini menggunakan metode kualitatif deskriptif, dengan data yang dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa perayaan Khanduri Beureuat merupakan tradisi masyarakat Muslim di Aceh, khususnya di Gampong Uteuen Gathom, Kabupaten Bireuen, yang dilaksanakan secara turun-temurun. Tradisi ini mengandung berbagai nilai seperti nilai ajaran Islam, kemanusiaan, moral, dan kebudayaan, serta mempererat hubungan kekeluargaan, solidaritas, dan menguatkan silaturahmi antar warga Gampong Uteuen Gathom, Bireuen, Aceh.